Together, but Still Separated? Migration Policy in the V4 countries - Glied Viktor (Sciendo, 2021)
The migration policies of the V4 countries present many similarities that seem to be the effect of congruent historical and economic determinants. During the migration crisis in 2015–2016, the Visegrad states partially coordinated their political communication using the same communication panels, which strongly impacted domestic political relations. The V4’s approach was a refusal of the open-door policy promoted by Germany and Sweden, and the European Union. Our main findings are that the migration crisis strengthened the cohesion among V4 countries, although the source of this cohesion was clearly a populistic stance toward the possible implications of uncontrolled migration (migrants and refugees). This communication style and the resulting political tensions were reflected in the V4 states’ resentment based on a sense of shared historical experiences rooted in Central European location and shared experience of the repercussions of communism. In this sense, a strong commitment to the idea of a sovereign nation-state, and a reluctance towards postmodern values are also important factors. This study charts the changes in V4 migration policy since 2015, highlighting the crucial developments in V4 countries’ negotiations with the European Union. It also deals with the foreign and domestic effects of the migration crisis and the V4 states’ discourse of migration, which was complemented by a debate on the future of the EU that became especially important in Hungary and Poland.